2022
DOI: 10.1002/oby.23365
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐122 promotes adipogenesis and aggravates obesity through the VDR/SREBF1 axis

Abstract: Objective This study examined the effects of miR‐122–enriched exosomes on the expression of vitamin D3 receptor (VDR) and sterol regulatory element‐binding transcription factor 1 (SREBF1) and their roles during adipogenesis. Methods The roles of miR‐122, SREBF1, and VDR were investigated during adipogenesis. The relationships between VDR and miR‐122 or SREBF1 were assessed by dual‐luciferase reporter and chromatin immunoprecipitation assays. The potential role of miR‐122/VDR/SREBF1 was evaluated in high‐fat di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Remarkably, miR-122 and miR-192 are strongly associated with cardiometabolic diseases—particularly T2D and MAFLD—in humans [ 53 , 54 , 55 ]. Recent data show that miR-122 promotes hepatic lipogenesis by targeting Sirt1 [ 56 ], whereas its inhibition in vitro in 3T3-L1 cells decreased Srebf1 [ 57 ]. We observed significantly increased Sirt1 and decreased Srebf1 in the liver and significantly increased Sirt1 and a tendency to decrease Srebf1 in the sWAT of EV mice—the two tissues that responded best to the EV-miRNAs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, miR-122 and miR-192 are strongly associated with cardiometabolic diseases—particularly T2D and MAFLD—in humans [ 53 , 54 , 55 ]. Recent data show that miR-122 promotes hepatic lipogenesis by targeting Sirt1 [ 56 ], whereas its inhibition in vitro in 3T3-L1 cells decreased Srebf1 [ 57 ]. We observed significantly increased Sirt1 and decreased Srebf1 in the liver and significantly increased Sirt1 and a tendency to decrease Srebf1 in the sWAT of EV mice—the two tissues that responded best to the EV-miRNAs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many other regulators also play a part during this process, including sterol regulatory element-binding transcription factor 1c (SREBF1c), STAT5, and delta-like 1 (DLK1) [ 133 , 134 , 135 ]. In addition, there is evidence both in vivo and in vitro that VDR interacts with other regulators and influences the progression of adipogenesis, although these results are inconsistent [ 136 , 137 , 138 ].…”
Section: The Effects Of Maternal Vd Deficiency On Offspring Obesity A...mentioning
confidence: 99%
“…Compare with control cells, high levels of miR-122 were found only in adipose tissue-derived exosomes (EXs-AT) and EXs-AT-treated cells. Overexpression of miR-122 promoted adipogenesis, while miR-122 inhibition prevented adipogenesis by regulating VDR, SREBF1, PPAR-γ, LPL and adiponectin ( 57 ). Our previous results in vitro study also showed that overexpressed miR-130b could be successfully packaged into EXs, and EXs-miR-130b could be taken up into porcine subcutaneous preadipocytes and inhibited the adipogenic differentiation by inhibiting the expression of PPAR-γ and its related genes ( 49 ).…”
Section: Exs-derived Mirnas Regulate Adipogenic Differentiationmentioning
confidence: 99%